COVID-19 in patients with chronic lymphocytic leukemia: a multicenter analysis by the Czech CLL study group - Šimkovič, Martin; Turcsányi, Peter; Špaček, Martin; Mihályová, Jana; Ryznerová, Pavlína; Maco, Mária; Vodárek, Pavel; Écsiová, Dominika; Poul, Hynek; Móciková, Heidi; Zuchnická, Jana; Panovská, Anna; et al. (Annals of hematology, 2023)
Patients with chronic lymphocytic leukemia (CLL) have a high risk of poor outcomes related to coronavirus disease 2019 (COVID-19). This multicenter cohort study evaluated the impact of COVID-19 infection on the population of CLL patients in the Czech Republic. Between March 2020 and May 2021, 341 patients (237 males) with CLL and COVID-19 disease were identified. The median age was 69 years (range 38-91). Out of the 214 (63%) patients with the history of therapy for CLL, 97 (45%) were receiving CLL-directed treatment at diagnosis of COVID-19: 29% Bruton tyrosine kinase inhibitor (BTKi), 16% chemoimmunotherapy (CIT), 11% Bcl-2 inhibitor, and 4% phosphoinositide 3-kinase inhibitor. Regarding the severity of COVID-19, 60% pts required admission to the hospital, 21% pts were admitted to the intensive care unit (ICU), and 12% received invasive mechanical ventilation. The overall case fatality rate was 28%. Major comorbidities, age over 72, male gender, CLL treatment in history, CLL-directed treatment at COVID-19 diagnosis were associated with increased risk of death. Of note, concurrent therapy with BTKi compared to CIT was not associated with better outcome of COVID-19.
Keywords: Cohort Studies; COVID-19 Testing; mužské pohlaví; Male; chronická lymfatická leukemie; Czech Republic; senioři; senioři nad 80 let; Humans; Female; kohortové studie; lidé; COVID-19; Middle Aged; ženské pohlaví; lidé středního věku; Česká republika; fosfatidylinositol-3-kinasy; Aged, 80 and over; Leukemia, Lymphocytic, Chronic, B-Cell; dospělí; Phosphatidylinositol 3-Kinases; Adult; Aged; testování na COVID-19